PENERAPAN TEKNIK DiET BOS UNTUK MENINGKATKAN KEMAMPUAN MENYIMAK SISWA KELAS IX A2 SMP NEGERI 1 SINGARAJA - Putu Ira Sita; Saliman Saliman (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2019)
This study aims to improve the ability of English listening skills toward the grade IX A2 students of SMP Negeri 1 Singaraja through DiET BOS technique. The study used a classroom action research design. The subjects of this study were the 29 students of grade IX A2 at SMP Negeri 1 Singaraja in Academic Year 2017/2018. The data were analyzed using descriptive statistics. The data analysis revealed that the mean score of students’ ability in listening to the text in the first cycle is equal to 77,93 and the mean score of students’ ability in listening to the text in the second cycle is 86,21. Based on those findings, it can be concluded that the students’ listening skill in the first cycle to the second cycle has increased to 8,28. According to the data analysis results and the discussion, it can be summarised that the students’ listening skills to the text have increased significantly by the application of the DiET BOS technique in the first cycle to the second cycle.